MODAL SOSIAL PEMBUDIDAYA IKAN PADA UNIT PEMBENIHAN LELE ALASKOBAR FARM DI DESA PANDAU JAYA KECAMATAN SIAK HULU, KABUPATEN KAMPAR - Yuni Dawati Naibaho; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at the Alaskobar Farm Hatchery unit in Pandau Jaya Village, Siak Hulu Subdistrict, Kampar regency with the aim of knowing how social capital is used and how they maintain social capital. This study uses descriptive qualitative methods with primary data sources, namely interviews with 6 informants, namely business owners, workers, and consumers. Data collection techniques are carried out with observation, interviews and documentation. The sampling technique used is purposive sampling. Data analysis uses interactive analysis, namely data collection, data reduction, data presentation, and conclusion withdrawal. The results of this study show that social modes consisting of networks, norms, and beliefs are sociological capital that are very influential in the success of a business, especially in the Alaskobar Farm hatchery unit in Pandau Jaya Village. Social capital has a very important role in the development and success of the hatchery business. Social capital has an important role in every aspect of cultivation activities including the expansion of the market through existing networks. An extensive network can make it easier for cultivators to market their cultivation. The network enables them to see current market opportunities, and helps them to obtain information related to the world of fisheries, especially catfish. Not only the network, the norm also takes part in cultivation activities. With the norm, cultivation activities can run well without any obstacles. Trust is also an important part of making Alaskobar Farm a successful hatchery unit to date. The existing social capital is maintained by running and reassessing the social capital, namely networking, norms and beliefs and maintaining the quality of cultivation and services provided to everyone who comes to Alaskobar Farm.Keywords: Social Capital, Cultivators, Seeding